INTEGRATING POLICY, HEALTH, AND SOCIOCULTURAL DIMENSIONS IN MARRIAGE AND REPRODUCTIVE HEALTH: A SYSTEMATIC LITERATURE REVIEW - Bernadetta Dara Pandu Pertiwi; Maesaroh Maesaroh; Djoko Siswanto Muhartono; Sunee Hongwiset (Institut Riset dan Pengembangan Indonesia, 2026)
Marriage and reproductive health issues are multidimensional issues influenced by the interaction between policy, health, and sociocultural factors. However, most studies still examine these three dimensions separately, thus failing to provide a comprehensive understanding. This study aims to identify, map, and synthesize literature on marriage and reproductive health through an approach that integrates policy, health, and sociocultural dimensions. The study used the Systematic Literature Review (SLR) method with reference to the PRISMA 2020 guidelines. Articles were obtained from the Scopus database for the 2015–2025 period. Of the 167 identified articles, 21 met the inclusion criteria and were analyzed thematically. The results indicate that the literature can be grouped into three main themes: policy interventions and child marriage, premarital screening and reproductive health, and changes in attitudes toward premarital sex and marriage. The most dominant themes include knowledge, attitude, practice, policy, screening, marriage, and child marriage. These findings indicate that policy success is determined not only by regulations, but also by the quality of implementation, health literacy, and public acceptance of the program. This research contributes by offering a perspective that integrates policy, health, and sociocultural dimensions as a basis for developing more comprehensive marriage and reproductive health policies.